2007
DOI: 10.1016/j.bbmt.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hematopoietic Cell Transplants Using Plasma-Depleted Cord Blood Products That Are Not Red Blood Cell Reduced

Abstract: Limited cell dose hampers wider use of cord blood transplantation (CBT). By depleting plasma but not RBC during processing, nucleated cell (NC) loss is reduced to <0.1% which increases significantly the proportion of high cell dose products-3-fold for products with NC >or=200 x 10(7). Clinical outcome for plasma depleted (PD) CBT was previously unavailable. A retrospective audited analysis was performed on 118 PD CBT, with mean and median NC doses of 7.6 x 10(7)/kg and 5.6 x 10(7)/kg, respectively, for this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…The very low CFU numbers obtained from PD grafts may be related to our washing method used being suboptimal for these types of units [40].…”
Section: Discussionmentioning
confidence: 99%
“…The very low CFU numbers obtained from PD grafts may be related to our washing method used being suboptimal for these types of units [40].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported that a post-thaw cord blood dextran albumin based washing, was important to maintain cord blood progenitor cell viability and to speed engraftment. However, recent clinical studies show that post-thaw cord blood dilution without washing, or even direct infusion of thawed cord blood is associated with equally reliable engraftment and freedom from side effects [41].…”
Section: Cord Blood Bankingmentioning
confidence: 99%
“…9 An alternative method is to deplete plasma but not red blood cells so that entrapment of nucleated cells, and possibly progenitor and stem cells is avoided, with some degree of volume reduction associated with the removal of plasma. 10,11 …”
Section: Introductionmentioning
confidence: 99%